Optogenerapy: When bio‐electronic implant enters the modern syringe era. Issue 5 (September 2017) - Michel, Fanny; Folcher, Marc
Abstract : Abstract : Resort to medications dates back million years ago with the use of medicinal plants. In the nineteenth century, significant contributions in medicine appeared in different domains, among which the invention of a specific drug delivery device; the syringe. Nowadays, injection therapy of bio‐manufactured drugs is routine practice for chronic diseases but remains constraining and painful. New emerging advanced therapies invest in genetic, electronics and cell‐based therapy for addressing unmet needs for the caregivers and the patient. As digital process in health (eHealth) gains momentum, connected advanced bio‐electronic devices now offer new strategies for personalized injection therapies. In this review, we take a journey along the genesis path of a new drug delivery system: the Optogenerapy, a synergy between optogenetic and gene therapy. Inside a bio‐electronic implant, electronics and optogenetics are interfaced by light as a traceless inducer signal. By controlling a synthetic optogenetic pathway in the cell, therapeutics delivery can be fine‐tuned with a precise spatiotemporal control. The technology holds promise of a new modern syringe era capable of producing a drug of interest at will directly inside the patient.